Experimental investigation and optimization of micro-drilling parameters on Inconel 800 superalloy. Issue 11 (17th August 2020) - Venkatesan, K.; Devendiran, S.; Bhupatiraju, Sai Chandra Sekhara Raju; Kolluru, Sathwik; Pavan Kumar, Chirla
ABSTRACT: This work presents the experimental study and optimizing the micro-drilling parameters on geometrical accuracy in micro-drilling on Inconel 800. The geometrical accuracy of the holes is incorporating circularity, overcut, hole damage factor, and taper ratio. In addition to that, material removal rate, machining time, and temperature are taken for study. Micro-holes, based on Taguchi orthogonal array (L27 ) design, are drilled on the workpiece of 2 mm thickness using uncoated tungsten carbide tools. Medium tool diameter, low spindle speed, and high feed rate resulted in the reduction in the magnitude of machining temperature, machining time, minimum circularity, overcut, hole damage factor, and taper ratio with increased material removal rate. The feed rate, tool diameter, and spindle speed are the order of the influencing parameter on the geometrical accuracy of the hole. The number of holes drilled before tool breakage is 120 in magnitude. Further, the increase in circularity error by 1.12%, overcut, and taper ratio decrease by 60% and 25% from 1 st to 120 th hole at an optimal level of medium tool diameter, low speed, and high feed rate. From the investigation, 0.8 mm tool diameter can be chosen for micro-drilling of cooling holes in jet engines, printed circuited boards, and biomedical elements.